Physical activity, air pollution, and incident long-term conditions: a prospective cohort study - Minshan Huang; Jonathan R. Olsen; Stewart G. Trost; Carlos Celis-Morales; Jill P. Pell; Frederick K. Ho (BMC Medicine)
Abstract Background Physical activity (PA) is consistently associated with lower risk of long-term conditions. Preliminary evidence suggested the associations could be modified by air pollution. This study aims to examine whether air pollution levels modify the associations of PA with all-cause mortality and incident cancer, major adverse cardiovascular events (MACE), type 2 diabetes, and chronic obstructive pulmonary disease (COPD). Methods A total of 414,644 UK Biobank participants were included in the analyses. PA was self-reported and objectively measured using accelerometers. PA was self-reported with IPAQ and objectively measured using accelerometers. Annual PM2.5, PM10, and NO air pollutant concentrations in 2010 were measured using a European land use regression model. Cox proportional hazard models were used to examine the associations of PA and air pollution with health outcomes. Multiplicative and additive interactions were estimated. Results During the study period from 2006 to 2022, 31,765 (7.7%) died, 70,299 (17.0%) had incident cancer, 25,130 (8.5%) had type 2 diabetes, 33,284 (8.0%) had MACE, and 18,844 (4.5%) had COPD. Lower PA was associated with higher risk of all health outcomes. Higher concentration of PM2.5 was associated with all outcomes except for cancer. The associations of self-reported PA with mortality and cancer were stronger in areas with higher air pollution with significant additive and multiplicative interactions. There was no evidence of moderation for objectively measured PA. Conclusions In the UK, air pollution should not be a factor inhibiting the promotion of PA.